Subgroup Analysis of Patients with Cancer in XALIA: A Noninterventional Study of Rivaroxaban versus Standard Anticoagulation for VTE - Ageno, Walter; Mantovani, Lorenzo G.; Haas, Sylvia; Kreutz, Reinhold; Monje, Danja; Schneider, Jonas; van Eickels, Martin; Gebel, Martin; Turpie, Alexander G. G. (TH Open, 2017)
Background The noninterventional XALIA study compared rivaroxaban with standard anticoagulation for deep vein thrombosis treatment. This substudy describes the demographics, clinical characteristics, and outcomes of the patients with cancer.Methods Therapy type, dose, and duration were at the physician's discretion. The cohorts identified were rivaroxaban (rivaroxaban alone or after heparin or fondaparinux for ≤48 hours); early switchers (rivaroxaban after heparin or fondaparinux for >48 hours to 14 days and/or a vitamin K antagonist [VKA] for 1–14 days); standard anticoagulation (heparin or fondaparinux and a VKA); low-molecular-weight heparin (LMWH) alone; and miscellaneous (other heparins, fondaparinux alone, VKA alone). Primary outcomes were major bleeding, recurrent venous thromboembolism, and all-cause mortality.Results In XALIA, 587 patients (11.4% of the XALIA cohort) were with cancer: 146 (24.9%) rivaroxaban, 30 (5.1%) early switchers, 141 (24.0%) standard anticoagulation, 223 (38.0%) LMWH, and 47 (8.0%) miscellaneous. Patients with gastrointestinal or lung cancer more commonly received LMWH than rivaroxaban; the opposite occurred in patients with breast or genitourinary cancer. Rates of primary outcome in the rivaroxaban group were as follows: major bleeding, 1.4% (n = 2); recurrent venous thromboembolism, 3.4% (n = 5); and all-cause mortality, 4.8% (n = 7).Conclusion In XALIA, physicians treated cancer-associated thrombosis with various anticoagulant regimens, most commonly LMWH. In addition, the choice of anticoagulant varied with cancer type. In rivaroxaban-treated patients, rates for the primary outcomes were low, suggesting that patients administered rivaroxaban were a good prognosis group.
Keywords: cancer-associated thrombosis; low-molecular-weight heparin; rivaroxaban; routine clinical practice; venous thromboembolism